As manobras do comportamento desviante - Mânica, Jaqueline Maia (2012)
Having the intention of being vigilant upon the commitment of working towards people s and workers welfare when one makes the choice of getting into human science does not mean those professionals may have blurry lenses when it comes to the perception of facts and behaviors, or that they may adopt reductionist concepts of individual s expressions. This study, focused on different parking lot companies, opens a dialogue to understand the different and possible meanings of deviant behavior within working environments, between the different authors who are around, and who diverge within those contexts, by intertwining social markers aspects such as class and generation, frequent in those interactions. The ethnographic study carried on in the researched companies present the countless strategies workers of that professional category use to assure their space and to give voice to their needs in professional environments that provide a relative autonomy, and do not work with alterity.